Novel therapeutic targets and agents for pediatric dyslipidemia. (November 2021) - Sunil, Bhuvana; Foster, Christy; Wilson, Don P.; Ashraf, Ambika P.
Landmark studies have convincingly demonstrated that atherosclerosis begins in youth. While generally asymptomatic, an increasing number of youth with disorders of lipid and lipoprotein metabolism, such as familial hypercholesterolemia, are being identified through selective and universal screening. While a heart healthy lifestyle is the foundation of treatment for all youth with dyslipidemia, lipid-lowering therapy may be required by some to prevent morbidity and premature mortality, especially when initiated at a young age. When appropriate, use of statins has become standard of care for reducing low-density lipoprotein cholesterol, while fibrates may be beneficial in helping to lower triglycerides. Many therapeutic options commonly used in adults are not yet approved for use in youth less than 18 years of age. Although currently available lipid-lowering therapy is well tolerated and safe when administered to youth, response to treatment may vary and some conditions lack an efficient therapeutic option. Thus, newer agents are needed to aid in management. Many are in development and clinical trials in youth are currently in progress but will require FDA approval before becoming commercially available. Many utilize novel approaches to favorably alter lipid and lipoprotein metabolism. In the absence of long-term outcome data of youth who were treated beginning at an early age, clinical registries may prove to be useful in monitoring safety and efficacy and help to inform clinical decision-making. In this manuscript, we review currently available and novel therapeutic agents in development for the treatment of elevated cholesterol and triglycerides.